Utilization of Waste Material in Construction Industry : A Review - Swity Ahirwar; Ravindra Kumar Raj (International Journal of Scientific Research in Civil Engineering, 2021)
In the modern scenario, desires from concrete have expanded exponentially, different physical parameters of concrete like strength, durability, serviceability and cost needs change i.e. how successfully we can save the cost of cement without bargain the strength and durability of cement [1]. To defeat the inflation, supplementary cementitious material is utilized as a part of conjunction with OPC so that the durability, maintainability and cost effective can be accomplished. In India, 7.8 million ton GGBS as a by-product obtain in the manufacturing in the blast furnace. As the project financial development and improvement in the steel businesses the measure of generation is probably going to increment numerous folds [2-3]. Because of exponential developing in urbanization and industrialization by item from the steel businesses, for example, GGBS is turning into an expanding worry for reusing and waste material. Being a result utilizing it successfully up to some degree fills in as a stage for a green situation and at a same time remembering that the quality of cement doesn’t debased by the use of GGBS. In this paper we presenting review of literatures related to experimental investigation of concrete.